Implementasi CEDAW tentang Penghapusan Diskriminasi Perempuan : Studi Kasus Pemilu di Indonesia Tahun 2009 dan 2014 - Angelia Maria Valentina; Elisabeth Dewi (Jurnal Ilmiah Hubungan Internasional, 2017)
United Nations as international organization issued an international convention to eliminate discrimination towards women, called CEDAW (Convention on Elimination of All Form of Discrimination Against Women). As the one of the nation that ratified the convention, Indonesia, adopted CEDAW articles that becomes UU RI No. 7 Tahun 1984. Indonesia agreed to prevent further discrimination towards women and implement all the policies written on those article. Unfortunately, the success and implementation of CEDAW is still doubtful, especially in political realm. The number of women political participation never reached 30% according to the affirmative action that is stated in Indonesian Constitution. The 2009 and 2014 general election showed that women’s representation in parliament in still low and not having significant change. The success of CEDAW can be seen from women’s political participation, measured by international indicator called GEM (Gender Empowerment Measure). GEM is used to measure shift and effectiveness of the implementation of CEDAW Convention in Indonesia, especially in political participation. This article concluded that CEDAW International Convention in political participation is not effective yet, considering the number of women in parliament not balanced with ratio of women citizen in Indonesia.